Disobedient Markets: Street Vendors, Enforcement, and State Intervention in Collective Action. (September 2017) - Hummel, Calla
At 50% of the global workforce, informal workers constitute a large, diffuse, and resource-poor group with high barriers to collective action. Contrary to scholars' expectations, informal workers organize to varying degrees in most countries, and states often encourage them to do so. Why do some informal workers organize while others do not? I argue that states can intervene in informal workers' collective action decisions: As enforcement costs increase, states may pay informal workers to organize, and then bargain with the resulting organization over self-regulation. I present a game theoretic model of state intervention in collective action and illustrate it with original ethnographic, survey, and interview evidence from street markets in La Paz, Bolivia. I suggest that informal workers interact strategically with states and conclude with implications for formalization policies.